A corpus-based analysis to restructure the position of the core meaning of setia - Isam, Hishamudin; Mat Awal, Norsimah (Pusat Pengajian Bahasa & Linguistik FSSK UKM, 2011)
Speakers’ creativity in manipulating lexical usage has resulted in the emergence of new meanings and these meanings have the potential to be recorded in dictionaries. This emergence, therefore, calls for the restructuring of the new meanings to determine the position of the existing meaning vis-ti-vis the new meanings. The restructuring process should begin by analyzing the position of the core meaning of the lexical item; whether the position should be maintained or replaced with the peripheral or new meanings or dropped altogether as it has no relevance to the current situation. This study attempts to restructure the core meaning associated with values specifically the value of setia (loyal). The analytical procedure begins by analyzing every sentence in the selected corpus that has the lexical item setia. The lexical meanings are determined from the context of usage. Every meaning that is predicted and discovered is then categorized based on the domains of its usage. The categorization process displays the most frequently used meaning, and identifies meaning that is predicted to be more effective or better able to explain other meanings. Findings from the research show that the core meaning of the lexical item setia (loyal) remains in the metaphorical form teguh hati (unwavering loyalty). Based on the corpus examined, it is discovered that not only the core meaning is expanded to other peripheral meanings but that there are proofs that could explain the motivation of the conceptual structure in deciding teguh hati (unwavering loyalty) as the core meaning of the lexical setia (loyal).